2018
DOI: 10.1055/s-0037-1618593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Acetylserotonin on TLR-4 and MyD88 Expression during Intestinal Ischemia-Reperfusion in a Rat Model

Abstract: Treatment with NAS is associated with downregulation of TLR-4, MyD88, and TRAF6 expression along with a concomitant decrease in intestinal mucosal injury caused by intestinal IR in a rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Furthermore, AS-IV, bicyclol, SAB, and dioscin all played protective roles in cerebral IRI by inhibiting the TLR4/MyD88/TRAF6/NF-κB axis (Zhang et al, 2013;Tao et al, 2015;Wang et al, 2016;Li M. et al, 2017; Figure 4). Additionally, the latest research showed that TRAF6 was also involved in the regulation of aloin and NAS preconditioning to reduce liver and intestinal IRI, respectively (Du et al, 2019;Sukhotnik et al, 2019; Figure 4). The above research indicated that TRAFs have received much attention in the treatment of IRI, and new treatment methods and related mechanisms have been continuously discovered.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, AS-IV, bicyclol, SAB, and dioscin all played protective roles in cerebral IRI by inhibiting the TLR4/MyD88/TRAF6/NF-κB axis (Zhang et al, 2013;Tao et al, 2015;Wang et al, 2016;Li M. et al, 2017; Figure 4). Additionally, the latest research showed that TRAF6 was also involved in the regulation of aloin and NAS preconditioning to reduce liver and intestinal IRI, respectively (Du et al, 2019;Sukhotnik et al, 2019; Figure 4). The above research indicated that TRAFs have received much attention in the treatment of IRI, and new treatment methods and related mechanisms have been continuously discovered.…”
Section: Perspectivesmentioning
confidence: 99%
“…Meaningfully, many drugs or compounds can reduce cerebral IRI targeting the axis, including Astragaloside IV (AS-IV), bicyclol, salvianolic acid B (SAB), and dioscin ( Zhang et al, 2013 ; Tao et al, 2015 ; Wang et al, 2016 ; Li M. et al, 2017 ; Figure 4 ). Moreover, aloin and N-Acetylserotonin (NAS) were respectively involved in the regulating of liver and intestinal IRI by targeting TRAF6 ( Du et al, 2019 ; Sukhotnik et al, 2019 ; Figure 4 ), which provides targets for clinical treatment of liver and intestinal IRI-related diseases. In addition, miRNA-based treatments for IRI are very popular in recent years ( Huang Z. et al, 2019 ; Liang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…While 5-HT predominantly exerts proinflammatory effects, emerging evidence points to the anti-inflammatory and anti-oxidant effects of its endogenous fatty acid-conjugates, Nacyl 5-HTs, present in the gut [38][39][40][41]138]. Our laboratory uncovered that docosahexaenoylserotonin (DHA-5-HT), the conjugate of 5-HT with the n-3 poly unsaturated long chain fatty acid (LC PUFA) DHA, has anti-inflammatory effects both in mouse macrophages as well as in human peripheral blood mononuclear cells (PBMCs), by attenuating release of key inflammatory mediators [40,41].…”
Section: Fatty Acid-5-ht Conjugates With Immune-modulatory and Anti-omentioning
confidence: 99%
“…Furthermore, N-acyl-5-HTs with varying fatty acid moieties were reported to exert anti-inflammatory, anti-oxidant, and neuroprotective effects in a number of in vivo animal disease models [38,39,[142][143][144][145]. In an inflammatory in vivo gut model, the SCFA conjugate of 5-HT, N-acetyl-5-HT (also called NAS), has been shown to prevent gut mucosal damage and inhibit programmed cell death following intestinal ischemia-reperfusion (IR) in rats [38].…”
Section: Fatty Acid-5-ht Conjugates With Immune-modulatory and Anti-omentioning
confidence: 99%
See 1 more Smart Citation